A Systematic Review on Digital Investment Platform Adoption Through the Lens of Technology, Risk, Trust, Quality, and User Experience Dimensions - Karisma Nabil Santosa; Reny Nadlifatin; Apol Pribadi Subriadi (Journal of Information Systems Engineering and Business Intelligence, 2026)
Background: Digital investment platforms are growing rapidly, accompanied by great interest in adoption from the younger generation who are accustomed to using technology. However, existing research is still limited to instrument-specific analyses and not platform-specific ones, thus limiting a comprehensive understanding of broader adoption determinants. Objective: This study systematically reviews empirical research on the adoption of digital investment platforms by identifying the types of platforms studied, the most frequently used theoretical models, and the key determinant thematic groups influencing adoption across investment platforms. Methods: The Preferred Reporting Items for Systematic Literature Review guidelines were used to conduct the systematic literature review. VOSviewer was also used for bibliometric analysis to identify trends through keyword co-occurrences. Of the total 7,727 articles, 42 studies collected from 2020 to 2025 resulted in 42 studies that met the inclusion criteria. Results: The included literature focused on stock, cryptocurrencies, peer-to-peer lending, crowdfunding, mutual funds, and e-gold platforms. The most widely used theoretical frameworks were the TAM- and UTAUT-based models. The thematic synthesis revealed five key determinants that influence the adoption of digital investment platforms: technology adoption, risk, trust, quality, and user experience. Conclusion: This research demonstrates that the included literature forms an integrative framework for digital platform investment instruments that reveals that risk, trust, quality, and user experience are interrelated rather than a stand-alone dimension. This is often underemphasized and fragmented in previous adoption models. The new framework provides a foundation for future empirical validation, particularly for investment platforms that offer multiple instruments within a single digital service.   Keywords: Digital Investment Platforms, User Adoption, Risk, Trust, Quality, Systematic Literature Review